Physical Distancing is Better than Social Distancing”: A Breakdown of the Shift in Society’s Psychology and Behaviour - Khandal, Urvashi; Raghuvanshi, Lakhan; Gaur, Rajshri; Verma, Amit (Indian Journal of Community Health, 2024)
This study focuses on social and physical distancing narratives during the outbreak of Covid-19 in India. Researchers have attempted to explore the trajectory of discursive practices that define social and physical distancing and its impact on human psychology. Further, the study looks at the communication strategies that have been mediated to create a mediatized reality focused on keeping a safe distance from one another to prevent the spread of the virus that caused self-isolation, compelled quarantine, and worry over health issues like psychological distress, Depression, and mental anxiety. Researchers have incorporated mediation, analyzing the narratives around societal and cultural practices that are integral to societal behavioral patterns. Implementing physical distancing in India happened because many communities understood social distancing along caste lines. Major highlights of the study are that despite the efforts made by the Government, media, and other institutions, discriminatory practices existed.